(Re)Discovering the Promise of Fraser? Labour Pluralism and Freedom of Association - Hastie, Bethany (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2021)
Section 2(d) of the Canadian Charter of Rights and Freedom, which guarantees freedom of association, has undergone substantial evolution at the Supreme Court of Canada in the past decade. In this article, I advance a purposive and pluralistic interpretation of section 2(d). I establish that section 2(d) communicates a bundle of rights available to collective workplace representation both within and beyond the traditional Wagner model of majoritarian, exclusive unionism. To support such an interpretation, I revisit the Supreme Court decision in Ontario (Attorney General) v. Fraser. I illustrate the commitment to labour pluralism advanced in Fraser and read the subsequent Supreme Court jurisprudence on section 2(d) in light of this commitment. Ultimately, this article aims to lay a robust foundation for further dialogue on the potential of freedom of association to effectively protect and advance labour rights in Canada in a plurality of contexts.